SMART AUTONOMOUS AGRICULTURAL SYSTEM FOR IMPROVING YIELDS IN GREENHOUSE BASED ON SENSOR AND IoT TECHNOLOGY - Djordjevic, Milos; Punovic, Vesna; Dankovic, Danijel; Jovicic, Branisal (Journal of Applied Engineering Science, 2020)
Agriculture and farm are some of the basic human lives that provide food, grains, and other raw materials needed for life. The subject of research is the observation and control of the microclimate using Internet of Things technology and smart sensor nodes. With increasing environmental pollution such as rivers, lakes, and most of the land that is the basis of agriculture, it is becoming increasingly difficult to grow healthy crops and therefore maintain a good yield. Technology development can play a huge role in protecting agricultural crops and reducing the additional labor required to keep agricultural yields at a level that meets the needs of today’s human lives. With a special focus on the now widespread Internet of Things (IoT) technology, it offers a convenient solution for smart agriculture. This paper will introduce a smart greenhouse monitoring and control data logger system as part of a smart farm. The system is based on: a group of built-in sensors, a microcontroller with a peripheral interface (PIC) as a core and a server system and a wireless Internet using the Global System of Mobile Telecommunications (GSM) module with General Packet Radio Service (GPRS) as a communication protocol. It is possible to implement a smart agricultural service, in which the realized smart data logger system could be implemented, which enables automatic control of the greenhouse at the farm.